Rapid diagnosis, treatment and follow-up of pedigrees with late-onset methylmalonic aciduria and homocystinuria cobalamin C type - Xiao-hui DUAN; Ying HAO; Wei-hong GU; Jin ZHANG; Ren-bin WANG (Chinese Journal of Contemporary Neurology and Neurosurgery, 2019)
Objective To summarize phenotype, treatment principles and prognosis of 4 patients from 2 pedigrees with late-onset methylmalonic aciduria (MMA) and homocystinuria cobalamin C (cblC) type, so as to explore the pathophysiological mechanism of this disease. Methods and Results Exome sequencing was applied to rapidly diagnose 2 pedigrees of late-onset MMA and homocystinuria cblC type. The MMACHC gene mutations of the sisters in pedigree 1 were exon 4 c.482G > A (p.Arg161Gln) and c.615C > A (p.Tyr205X). Their parents carried the gene mutation respectively. The proband presented intelligence deterioration, spastic motor dysfunction of lower limbs and epilepsy. The younger sister presented axonal peripheral neuropathy and optic nerve atrophy, while the mental retardation was mild. For the brother and sister in pedigree 2, c.440_441del (p.Gly147fs) and c.482G > A (p.Arg161Gln) in exon 4 of MMACHC gene were identified which came from their parents respectively. The proband presented mental retardation and behavior disorder, weakness of lower limbs with pyramidal sign, and myelinated and axonal mixed peripheral neuropathy. His younger sister had similar symptoms and suffered earlier. After treated by vitamin B12, folic acid and levocarnitine for 6 months, all patients showed intelligence improved and seizures controlled, while still suffered from different degrees of dyskinesia of lower limbs. Conclusions The clinical symptoms of late-onset MMA and homocystinuria cblC type are complex and variable. Cerebral cortex, pyramidal system, extrapyramidal system and peripheral nerve could be widely involved. Target region gene capture combined with next-generation sequencing technology can be used to diagnose the disease rapidly, and early diagnosis and treatment are crucial to improve the prognosis.